(untitled) (Damascus University Journal for engineering sciences, 2026)
The Construction Supply Chain CSC includes a spectrum of activities and stakeholders involved in construction projects, encompass a complex network of relationships, material flows, financial transactions, and information exchanges between designers, owners, contractors, and suppliers. CSC face numerous challenges. Therefore, effective management of the CSC emerges as a critical determinant for project success. The adoption of Internet of Things (IoT) technologies, such as Global Positioning System GPS and Radio Frequency Identification RFID, has revolutionized supply chain management in various industries. These technologies enable the tracking of materials, real-time monitoring of operations, and seamless data exchange. Consequently, research efforts have been directed towards investigating the application of IoT in the CSC. To address this research gap, a descriptive methodology was employed, encompassing a comprehensive review of existing literature and the design of a questionnaire. The collected data played a pivotal role in identifying the most significant obstacles impeding the CSC (waste) and determining the prevalent IoT tools employed in Syria (smart devices). Building upon these findings, a framework was developed within a computer cloud environment, incorporating five IoT tools. This framework elucidates the interconnectedness and roles of various stakeholders within the supply chain. Subsequently, the proposed framework was presented to experts to validate its feasibility and gather expert opinions. The experts confirmed the viability of the Framework, providing feedback for enhancement and identifying potential obstacles that may hinder its application in Syria.